Examining anxiety levels and self-efficacy in Pencak Silat athletes: A comparative study - Yusuf, Nur Raidha Ahadiyah; Fitri, Mustika; Hamidi, Ahmad; Apriady, Hilmy; Ockta, Yovhandra (UIR Press, 2025)
Background Problems: Anxious athletes often doubt their ability to manage stress and achieve goals. Developing self-efficacy is vital as it enhances performance and confidence while reducing stress. There is a research gap in exploring the relationship and differences between self-efficacy and pre-competitive anxiety across athletes in sports with varying characteristics. Research Objectives: Considering the lack of research on self-efficacy in Pencak Silat, this study aims to deepen understanding of how self-efficacy impacts performance, particularly when comparing individual and team categories in Pencak Silat. Methods: Sample selection used the Purposive Sampling technique, with criteria including individual and team categories in Pencak Silat consisting of 30 athletes, including 15 individual and 15 team categories from Pencak Silat PON Jawa Barat and PAL Kota Bandung athletes. The research design used is a correlation and comparative study, with data collection employing a quantitative method. The measurement tools used were the CSAI-2R and the GSES. The data were analysed using correlation tests to measure the relationship between anxiety levels and self-efficacy, and independent sample t-tests were used to compare differences between the two groups in terms of anxiety and self-efficacy level. Finding and Results: The results of the correlation test show that there is a relationship between anxiety and self-efficacy with the Pearson value for teams (-0.532) and individuals (0.771), and the results of the hypothesis show a significant difference between the two categories (0.001 < 0.05). Conclusion: The study found significant differences in anxiety and self-efficacy between individual and team pencak silat athletes, emphasising the need for tailored psychological approaches to enhance performance. Future research could explore targeted mental training programmes, track changes over time, or examine other martial arts or athlete groups for deeper insights.